P480 Evidence-based design for neonatal units: a systematic review. (June 2019) - O'Callaghan, Niamh; Dee, Anne; Philip, Roy K
Abstract : Background: Evidence-based hospital design could significantly improve patient safety and make patient, staff and family environments healthier. This systematic review aims to determine which neonatal intensive care unit design features lead to improved neonatal, parental and staff outcomes. Methods: Medline, CINAHL, Web of Science Citation Index and Cochrane Central Register of Controlled Trials Registry, were searched in January 2017. Using combinations of the relevant key words, review was performed following the recommended guidelines for reporting systematic reviews. English language limitation was applied and term limited to 2006–2016. Pre-piloted forms were used by one reviewer and cross verified by second reviewer. Included studies were assigned a grade based upon their level of evidence and critically appraised using defined tools. Data were not synthesized for metanlysis due to nature of literature reviewed and heterogeneity. Results: 3, 592 titles were screened with 43 full-texts assessed for eligibility. 30 studies were deemed eligible for inclusion. These included 19 cohort studies, two qualitative studies, seven cross-sectional studies, one systematic review (peer reviewed articles up to January 2011) and one randomised control trial. Grey literature search from guidelines, catalogues and repositories yielded additional 10 guidelines. Conclusions: Optimally designed neonatal unit has many possible health implications, including improved breastfeeding, infection and noise control, reduced length of stay, hospitalisation rates and potentially improved neonatal morbidity and mortality. 'Single family room' design for neonatal units is recommended. Consideration should be given to infection prevention and control, including sink frequency and positioning, and airborne isolation facilities. Support areas for families, staff and breastfeeding mothers are also recommended. High quality, family centred neonatal care could be assisted through well grounded, future proofed and technology enabled design concepts that have the potential to impact upon early life development. Nature of the topic poses inherent limitations for conduct of randomized trials; however observational studies using standardised methodologies could add further evidence.